2005
DOI: 10.1107/s160053680500680x
|View full text |Cite
|
Sign up to set email alerts
|

(Z)-2-(3-Thienyl)-3-(3,4,5-trimethoxyphenyl)acrylonitrile

Abstract: The title compound, C16H15NO3S, was prepared by base‐catalyzed reaction of 3,4,5‐trimethoxy­benzaldehyde with thio­phene‐3‐acetonitrile. The olefinic bond has Z geometry and thien­yl ring flip disorder is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The site occupancy factors refined to 0.847 (5) and 0.153 (5) for the S1-C15-C16-C17-C18 ring, and 0.700 (5) and 0.300 (5) for the S2-C20-C21-C22-C23 ring. A similar thiophene ring disorder has been observed in some thiophene derivatives, such as (Z)-3-(1-methyl-1H-indol-3-yl)-2-(thiophen-3yl)acrylonitrile (Sonar et al, 2004), (Z)-2-(3-thienyl)-3-(3,4,5-trimethoxyphenyl)acrylonitrile (Sonar et al, 2005a),…”
Section: Data Collectionsupporting
confidence: 67%
See 1 more Smart Citation
“…The site occupancy factors refined to 0.847 (5) and 0.153 (5) for the S1-C15-C16-C17-C18 ring, and 0.700 (5) and 0.300 (5) for the S2-C20-C21-C22-C23 ring. A similar thiophene ring disorder has been observed in some thiophene derivatives, such as (Z)-3-(1-methyl-1H-indol-3-yl)-2-(thiophen-3yl)acrylonitrile (Sonar et al, 2004), (Z)-2-(3-thienyl)-3-(3,4,5-trimethoxyphenyl)acrylonitrile (Sonar et al, 2005a),…”
Section: Data Collectionsupporting
confidence: 67%
“…For general background, see: Herrmann et al (1995); Herrmann (2002); Arduengo & Krafczyc (1998). For related compounds, see: Arslan et al (2007Arslan et al ( , 2005a and references therein; Sonar et al (2004Sonar et al ( , 2005a; Wagner et al (2006a,b); Crundwell et al (2002); Linehan et al (2003); Liu et al (2004); Navarro et al (2006); Therrien et al (2004). For bond-length data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%
“…The site-occupancy factors refined to 0.636 (3) and 0.364 (3) for ring A, and to 0.814 (3) and 0.186 (3) for ring B. A disorder of this kind has been observed in the structures of simple thiophene derivatives, for example, in a family of 3-thienylacrylonitriles (Sonar et al, 2004(Sonar et al, , 2005a, but it was not reported in the closely related structure of 2,5-bis(2thienylvinyl)thiophene (Zobel & Ruban, 1978).…”
Section: Commentmentioning
confidence: 96%
“…These two orientations are not equivalent; the site-occupation factors refined to 0.689 (3) and 0.311 (3). A disorder of this kind is often observed in the structures of simple thiophene derivatives with one substituent, for example in a family of thiophene-3-carboxamides (Howell et al, 2005) or in 3-thienylacrylonitriles (Sonar et al, 2004(Sonar et al, , 2005a.…”
Section: Commentmentioning
confidence: 99%